Optimalisasi Perencanaan Tambang Berdasarkan Pemilihan Kebutuhan Alat Berat Untuk Mencapai Target Produksi di Tambang Besar (TB 2.2) Tempilang Front 1 Kec. Tempilang Mitra PT Timah (Persero) Tbk - Supriyadi Supriyadi; Mardiah Mardiah; Abrianto Akuan (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2017)
Mining activities in TB 2.2 TempilangSite was conducted by Bahtera Sarindo Utama as a partner of PT Timah (Persero) Tbk.The method and technology used in mining site was Mechanical Mine as an alternative of conventional open pit mining which had been applied to overcome a great lack of hydraulic mining. There were several problems occurred in tin mining activities of TB 2.2 Tempilang included less of cycle time of gravel pump per day due to several problems that appeared in mine site such as gravel pump were often broken, Front Work landslides, so the production activity was inefficient. Mine planning of Mining mechanical methods plan Mechanics in TB 2.2 TempilangSite had production target of 320 m3 / h or 5,760 m3 / day. Therefore it was necessary to optimize the mining design to make it more efficient. The study included the election needs of load haulage equipment and conveyance based fleet to achieve production targets.Based on the results obtained, the need of equipment in hydraulic mine method for IDH work Front 1 to achieve production target was4 units of hydraulic pump, 4 units of gravel pump, 3 units of Excavators and 4 units of Articular Dump Truck with the total production of 5,976 m3 / day, and if using mechanical mine methodthe needs of load haulage equipment and conveyance for IDH removal was 1 fleet, 2 units of CAT 320D2 Excavator and 6 units of CAT 740B ADT with a total production of 6588.00 m3 / day with the production rate at 9.20 % greater than hydraulic mine and fleet 2 such us 1 unit of 345D CAT Excavator and 6 units of CAT 740B ADT 6 with the total production of 6468.12 m3/ day with the production rate at 7.60% greater than hydraulic mine.Based on the results obtained, mine lifetime of TB 2.2 TempilanFront 1 was 6,13 years using hydraulic mine method, 5,57 years for Mechanical mine of fleet 1 and 5.67 years for fleet 2. From these results suggested, that would better to use mechanical mine method in the removal of IDH in TB 2.2 Tempilang. With the availability of load haulage equipments and conveyance would counduct with fleet 1.